Molecular mechanism of the effect of benzene ring structure in nonionic surfactants on the wettability of anthracite - Li, Jiajun; Yan, Guochao; Zhou, Li; Bai, Xuyang; Chen, Xuanlai (Colloids and surfaces. A, Physicochemical and engineering aspects, 2023)
Reducing coal dust is critical for environmental protection and energy efficiency, however anthracite has a high degree of coalification, high hydrophobicity, resulting in a poor dust removal effect. The addition of surfactants to water can improve the wetting of coal dust, resulting in a more effective dust reduction effect. In this investigation, Polyethylene glycol octyl phenyl ether (Triton X-100) and The lauryl polyoxyethylene ethers (C12(EO)9) were chosen as research subjects. Contact angle experience, Fourier Transform infrared spectroscopy experience (FTIR), and X-ray Photoelectron Spectroscopy experience (XPS) were used to compare the ability of two surfactants to improve the wettability of anthracite from a macro perspective. Molecular dynamics (MD) simulation was used to explain macroscopic experimental phenomena from a microscopic perspective. Due to the presence of the benzene ring structure in the hydrophobic group, the surface of anthracite following Triton X-100 adsorption is more hydrophilic. The network structure of Triton X-100 molecules on the surface of anthracite is loose owing to the presence of the benzene ring, which facilitates water molecule penetration. [Display omitted]